Towards a common vision of climate, peace, security and migration in Mozambique: Workshop Memory - Synnestvedt, Thea; Sax, Niklas; Maviza, Gracsious; Caroli, Giulia; Tarusarira, Joram; Läderach, Peter (2023)
Mozambique is facing multiple climate and security-related risks, creating a complex climate security landscape with adverse impacts on human security. Sustained changes to average temperatures and rainfall variability affect rural livelihoods and food security, while extreme weather events such as cyclones, floods and droughts cause loss of lives, food supplies, housing and other infrastructure, deteriorating the security of people affected and inducing displacement. The implications of climate change on the local peace and security landscape are complex, yet closely interlinked. The Northern regions in Mozambique, particularly Cabo Delgado have been plagued by violence committed by non-state armed groups. The violence in the North coupled with increasing frequency and intensity of extreme weather events has generated mass displacement, leaving many people in insecure positions.